Mercantilização da saúde: uma análise dos processos de inclusão perversa representados pelos planos de assistência privada em saúde na cidade de São Paulo - Cadette Junior, Paulo (2019)
The purpose of this thesis is to evaluate the commodification of health represented by the existence of health plans in the city of São Paulo. The framework for the proliferation of private health plans in the city of São Paulo during the period from 2010 to 2016 is focused on quality in the privatization of health. We use the logic of the operation of private companies in the Brazilian medical sector and, above all, to understand the dynamics of inclusion of the citizens of São Paulo to these plans. In view of the existence of the SUS, which is a significant and significant advance in the direction of universal health care, the existence of these companies is at odds with what the Brazilian constitutional text says (Article 196 of 1988), "Health is everyone's right and duty of the State ... "? Due to the precariousness of the system, it makes those integrated into the labor market and higher incomes migrate to private plans. However, it can be noted from previous research and from what this investigation revealed that there is perverse inclusion, that is, that the situation in private plans after some time, resembles the conditions of the public health system. The objective of this study is to analyze the different forms of access to health services in private healthcare and hospital companies within the broader framework of deep social inequalities in Brazil. Specifically for the care given by users of the private system, relations between health care companies, we show the social stratification within the types of plans and health insurance. We analyze the different logics of workings, that is, different bureaucratic demands, monetary forms of management, entrepreneurial directives and their commercialization. As a form of homologation of the research, we created questionnaires for the user population as well as for health professionals. Perverse inclusion here considered as the inclusion in the health system with the perspective of having full service for all who participate with the insurance payment and that does not correspond to the reality because there are technical criteria of use and costs step as a way to regulate the investment in this area, the perverse inclusion that deceives people, makes us think that everything is working well and everything is moving toward respect for others, but it is not what always happens